Study on the Potential Use of the Aqueous Extract of Arabian Rose (Rosa Arabica) as an Insecticide and Plant Nutrient - Zeid,Alia. . . . . .; Aguieb, Radja; Khechekhouche, El Amine; Guehef, Zahra Hadda; Ghemam Amara, Djilani; Messaoudi, Mohammed; Cherrada, Nezar (Université de Carthage, 2025)
This study aims to investigate the potential use of the aqueous extract of Rosa arabica as both a plant nutrient and an insect repellent. The research was conducted in the Oued Souf region of Algeria. Rose water was tested as a plant nutrient by applying it to pumpkin seeds at different concentrations. The results showed significant differences in the germination and growth of the pumpkin seeds. Additionally, the aqueous extract of Rosa arabica was evaluated as a pesticide against aphids on oleander and vine plants and pea larvae. The results demonstrated promising effects, particularly on aphids and pea larvae. The aphids showed visible swelling and a color change from yellow to brown, while green aphids also turned brown. Regarding the pea larvae, they ceased feeding, swelled, and changed color from green to brown. Eventually, the brown larvae turned black and died, resulting in a significant mortality rate. The findings indicate that the aqueous extract of Rosa arabica exhibits a toxic effect on aphids in vineyards. As the extract concentration increased, the aphid mortality rate increased over time, reaching a maximum death rate of 95%. Moreover, our study confirmed that the aqueous extract of Rosa arabica has no harmful effects on plants. These results suggest that the aqueous extract of Rosa arabica effectively eliminates aphids and pea larvae, making it a safe and environmentally friendly biological control method. This natural alternative could replace chemical pesticides, which often have harmful environmental effects. الملخص تهدف هذه الدراسة إلى دراسة الاستخدام المحتمل للمستخلص المائي لنبات Rosa arabica كمغذي للنباتات وطارد للحشرات. تم إجراء البحث في منطقة واد سوف بالجزائر. تم اختبار ماء الورد كمغذي للنباتات من خلال تطبيقه على بذور اليقطين بتركيزات مختلفة. وأظهرت النتائج وجود فروق ذات دلالة إحصائية في إنبات ونمو بذور اليقطين. بالإضافة إلى ذلك، تم تقييم المستخلص المائي لنبات روزا أرابيكا كمبيد ضد حشرات المن على نباتات الدفلى والكروم ويرقات البازلاء. وأظهرت النتائج تأثيرات واعدة، خاصة على حشرات المن ويرقات البازلاء. أظهرت حشرات المن تورمًا واضحًا وتغيرًا في اللون من الأصفر إلى البني، بينما تحول لون حشرات المن الخضراء أيضًا إلى اللون البني. أما يرقات البازلاء فقد توقفت عن التغذية وانتفخت وتغير لونها من الأخضر إلى البني. وفي نهاية المطاف، تحولت اليرقات البنية إلى اللون الأسود وماتت، مما أدى إلى معدل وفيات كبير. تشير النتائج إلى أن المستخلص المائي لنبات Rosa Arabica يظهر تأثيرًا سامًا على حشرات المن في مزارع الكروم. ومع زيادة تركيز المستخلص، ارتفع معدل وفيات المن مع مرور الوقت، ليصل إلى معدل وفيات أقصى قدره 95%. علاوة على ذلك، أكدت دراستنا أن المستخلص المائي لنبات روزا أرابيكا ليس له أي آثار ضارة على النباتات. تشير هذه النتائج إلى أن المستخلص المائي للروزا العربية يقضي بشكل فعال على حشرات المن ويرقات البازلاء، مما يجعلها طريقة آمنة وصديقة للبيئة للمكافحة البيولوجية. وقد يحل هذا البديل الطبيعي محل المبيدات الحشرية الكيميائية، التي غالبا ما تكون لها آثار بيئية ضارة.
Intervention
Keywords: Aqueous extract of Rosa arabica; Aphids; Pea larvae; Plant nutrient; Biological control; المستخلص المائي للورد العربية; المن; يرقات البازلاء; المغذيات النباتية; المكافحة البيولوجية